Growth, Survival and Fecundity in Ornamental Fish, Betta splendens (Regan) as a Function of Stocking Density R. - R., James; K., Sampath (Fishery Technology, 2025)
Effects of stocking density (10,25,50,100 and 150 fish/501 ofwater) on growth, survival and fecundity were studied in Siamese fighting fish, Betta splendens. An increase in stocking density reduced the growth, survival and fecundity in B. splendens. A significant (P < 0.05) negative correlatibyi was obtained between density and feeding parameters or gonad weight or fecundity in B. splendens. Animals reared in higher densities elicited poor gonad development and it severely affected egg production and hatching. Accumulation of more ammonia and carbon dioxide and oxygen depletion with increase in stocking density could have reduced the feed consumption and growth which in turn affected the gonad development and fecundity in female B. splendens. However, fish reared in 10 and 25D groups could withstand ammonia stress of 1.01 mg l1 without any ill effect on survival, growth, gonad development and fecundity. Fish reared in 10 D group displayed better rates of feeding and growth at early rearing period than those in 25D group. However, fish reared in 25D group showed significantly higher growth rate (t=2.71; P